Perfectionism and Eating Disorders: Piloting an Indicated Internet Prevention Program for At-Risk Adolescents - O’Brien, Amy (Curtin University, 2023)
The aim of this research was to develop, trial, and review feedback on a co-designed, internet-based, indicated prevention program which used cognitive-behavioural therapy for perfectionism to reduce symptoms of eating disorders, perfectionism, and anxiety, in female adolescents who were at increased risk for eating disorders. A feasibility and acceptability study using mixed methods results demonstrated preliminary support for the use of online cognitive-behavioural therapy for perfectionism as an effective eating disorder prevention program.